Analysis of Water Shortage and Socioeconomic Impacts on Jujube Growers of Taluka Hyderabad Rural, Sindh Pakistan - Mohsin Ali Khatian; Moula Bux Peerzado; Arshad Ali Kaleri; Abdul Latif Laghari; Mukesh Kumar Soothar; Jay Kumar Soothar; EhsanElahiBanger (Journal of Basic & Applied Sciences, 2017)
Water plays a vital role not only for survival of human being but it is also important for crops, animal and every creature which lives on the universe. Therefore; water shortage has some negative impacts on socioeconomic condition of jujube growers. Jujube (Ziziphus jujube) locally called ‘Beer’, is a native fruit of South Asia. Produced in moderate regions of different countries in the world: such as China, India, Pakistan, Syria, Malacca, Australia and Malaysia, Afghanistan, Iran and Russia. China is perhaps the most important country for jujube cultivation, where it is known as the “Chinese dates”, with hundreds of varieties, some being seedless. the study was conducted at Taluka Hyderabad Rural. Samples were randomly carried out from six villages (ten growers from each village) were selected, so the total sample size was 60 in numbers. Results exposed that education level of growers were primary 48 percent, secondary 27 percent, higher 18 percent and illiterate 7 percent respectively. Pattern of farming of growers in study area states that majority 29 percent of producer’s were full time and 71 percent of respondents were part time engaged in jujube growers. Mostly 67 percent of jujube farmers belong to medium income group, 18 percent were high income group and 15 percent were very low income group. Canal water unavailability to growers was 43 percent in study area. So government should take action to provide them excess of water for earning maximum profit